Criação do protótipo do sistema e-commerce em um mercadinho de pequeno porte de Itacoatiara/AM - Alves, Bruno Lemos (Brasil, 2024)
E-commerce is a type of business in which products are bought and sold entirely over the internet. Therefore, all parts of the product purchase are online: product selection, choice of delivery address, payment method and purchase. In this business model, the only step that involves the use of physical space is the delivery of a physical product to the user. However, use is entirely over the internet. This work presents the E-commerce framework, focusing on application in the use of the website for companies. The study was carried out in a company Mercadinho, located in Amazonas, whose problem is few customers/consumers and the goal is to resolve this problem. Research data was also collected through participant observation and information made available by the company, which was designed to better understand how the organization experiences e-commerce culture. After its creation, the tool was very well accepted by the owner and the company, because through the established goal and application of the method, together with improvement actions, it was possible to meet the desired goal, even before all the proposed actions were completed, this demonstrates that the study and development of the work were useful to corroborate one of the process improvement practices through an E-commerce tool.